STARTUP PROJECT AS A FORM OF INNOVATIVE ENTREPRENEURSHIP DEVELOPMENT - Бєлялов, Талят Е.; Гірник, Ярослав С. (Journal of Strategic Economic Research, 2024)
The article defines the peculiarities of a startup as an innovative project, enabling the establishment of an effective management concept. It explores the essence of startups, analyzes management concepts of startup projects, highlights their specifics, advantages, and disadvantages. Researching the literature definitions of the concept ’startup’ led to conclusions regarding its features: a newly launched small business in the innovation sector, operating in an environment of rapid growth, scalability, and uncertainty, presented by a group of individuals or a new company. Identified key startup characteristics allow for the revelation of primary features influencing funding: analogy-based features include rapid growth and the idea of global scalability regardless of geographical boundaries, innovation, and operations in conditions of uncertainty. The analysis of financing aspects based on their core characteristics includes small and medium-sized businesses, rapid growth, the idea of global scalability independent of geographical boundaries, innovation, and conditions of uncertainty. It is substantiated that startup development can follow two paths according to its lifecycle theory: rapid growth and scalability, or default with subsequent liquidation or reorganization. The conducted analysis of startup financing specifics helped to define the concept of ’startup funding,’ based on researched characteristics, as well as on ’finance’ in a broad sense and ’funding innovative activities’ in a narrow context. It is argued that the mechanism of startup funding is complex, and a key component is financial relationships between entrepreneurs and investors. The activity of these parties is supported by ensuring the development of innovative activities: regulatory, legislative, personnel, etc. It is justified that Ukraine has significant potential for startup project development, thus requiring the establishment of appropriate legal foundations for their support, especially within universities and research institutions.